Identification and diversity analysis of cassiicolin-encoding gene of Corynespora cassiicola isolates from rubber tree in Indonesia - FETRINA OKTAVIA (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Oktavia F. 2020. Identification and diversity analysis of cassiicolin encoding gene of Corynespora cassiicola isolates from rubber tree in Indonesia. Biodiversitas 21: 3499-3507. Cassiicolin is an important effector of virulence process on the Corynespora cassiicola, plant-pathogen that causes Corynespora leaf fall disease in rubber tree. The study aimed to identify and analyze the genetic diversity of isolates from rubber plants in Indonesian based on cassiicolin encoding gene (Cas gene). Identification of Cas genes was performed using 12 pairs of primers on 23 isolates from rubber host clones. Only three pairs of primers were able to amplify the analyzed DNA, namely CasF20/CasR28, CasF19/CasR26, and CasF4/R16 which produced DNA fragments of 760 bp, 550 bp and 210 bp respectively in this study. BLAST analysis showed that 19 isolates carried a Cas5 gene. Three of the 19 DNA samples also contained a putative Cas3 or Cas4 gene. Four other isolates had no detectable Cas gene (Cas0). The genetic diversity based on the Cas gene showed that the isolates were grouped into three major clusters. ome isolates had high genetic similarity with outgroup isolates from China. There was not clear link between Cas gene with virulence profiles. The cassiicolin encoding gene information is useful for predicting the virulence of C. cassiicola isolates from Indonesia rubber plantation, so that the disease severity spreading in rubber plants can be early anticipated.